Development and validation of a sensitive sandwich ELISA for quantification of insulin-like growth factor 2 in goat milk - Yao Wang; Jing Liu; Yinting Hao; Jingyu Gong; Yaxian Shang; Mengdi Han; Dekun Chen; Jia Li (International Dairy Journal, 2026)

Lysosomal dysfunction contributes to lead (Pb) and high-fat diet (HFD)-induced neuronal apoptosis: A link with cathepsin B - Yongke Yuan; Mengchen Liu; Mengdi Zhai; Meijia Wu; Wenhui Zhang; Yongjuan Xin; Yue Ba; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (NeuroToxicology, 2026)

Combined effects of triclosan and nanoplastics on reproduction performance, population dynamics, and transcriptome regulation of rotifer (Brachionus plicatilis) - Jilong Ren; Yunhong Yang; Meng Dong; Xiaolei Wei; Xingru Guo; Mengdi Zhang; Jiaxin Yang; Cui Han (Environmental Pollution, 2026)

3D reconstruction of pore throat connectivity in Shale: An SAXS-MICP integrated framework - Linhao Zhang; Shu Jiang; Jiale Fu; Fei Xie; Zhile Han; Zihao Li; Mengdi Sun (Marine and Petroleum Geology, 2025)

Dynamic safety assessment of deployment operation of subsea shell using STAMP and DOOBN approach - Xinhong Li; Mengdi Yang; Ziyue Han (Process Safety and Environmental Protection, 2025)

Exploring protein-mediated quality control mechanisms in Rice cooking behavior: from static protein content to dynamic architecture - Mengdi Chen; Han Geng; Dong Wang; Jinhong Gou; Mingqin Li; Ting Li; Xinxia Zhang; Juan Li; Li Wang (Food Chemistry, 2025)

A double-antibody sandwich ELISA for sensitive and specific detection of insulin-like growth factor 1 in goat milk - Yaxian Shang; Yinting Hao; Jing Liu; Jingyu Gong; Yao Wang; Mengdi Han; Dekun Chen; Jia Li (Food Bioscience, 2025)

Generation of hydrogen peroxide by using solid CaCO3 suspension via two-electron water oxidation - Huimin Liu; Guanghui Luo; Qiaozhi Han; Yilin Li; Yonghao Shen; Siyu Guo; Xinyu Wei; Chengyu Duan; Mengdi Sun; Yang Peng; Zheshun Ou; Yinglong Lu; et al. (Chemical Engineering Journal, 2025)

Visualization study of multiphase flow in deep-sea mining based on dual-modality electrical tomography - Xuanhe Han; Yanlian Du; Mengdi Fu; Jingyu Zhu; Rongqian Ruan; Yijun Shen (Ocean Engineering, 2025)

Synthesis and anti-inflammatory activity of chromone-sulfonamide derivatives as COXs/iNOS dual-target inhibitors - Meng Qin; Tao Xing; Mengdi Zhang; Jiatong Han; Shuyan Yu; Jianping Chen; Yuheng Ma (Medicinal Chemistry Research, 2025)

Molecular characterization of Klebsiella pneumoniae in clinical bovine mastitis in 14 provinces in China - Maierhaba Wusiman; Jiakun Zuo; Yong Yu; Zhaoyang Lv; Mengdi Wang; Lianhua Nie; Xiuping Zhang; Jing Wu; Zihao Wu; Wei Jiang; Zihao Pan; Wei Zhang; et al. (Veterinary Research Communications, 2025)

Mediated self-assembled gold nanoclusters with mesoporous silica particles to boost fluorescence for enhanced on-site monitoring of organophosphate pesticides - Shun Wang; Yaqing Han; Mengdi Su; Hao Wang; Yuze Chen; Baoling Huang; Qian Bai; Mengke Wang (Food Chemistry, 2025)

Particle size is an important factor influencing the effects of biochar return to woodland soils: An evaluation from the perspective of sapling growth and soil microbial carbon processes - Xiaoyu Gao; Haoting Liu; Wenxuan Mei; Wenwen Zhang; Haoyu Dong; Xiaohua Fu; Mengdi Xie; Yujie Han; Lei Wang (Journal of Environmental Management, 2024)

Dual active sites of N-rich triptycene-based 2D conductive metal–organic framework with 3D extended structures in high-performance lithium-ion batteries - Kai Shi; Xiaobin Liu; Jingting Sang; Mengdi Zhang; Dandan Han; Junbo Gong (Chemical Engineering Journal, 2024)

A review of groundwater iodine mobilization, and application of isotopes in high iodine groundwater - Yulu Zheng; Haiming Li; Mengdi Li; Cuixia Zhang; Sihui Su; Han Xiao (Environmental Geochemistry and Health, 2024)

Unveiling the innovative green synthesis mechanism of selenium nanoparticles by exploiting intracellular protein elongation factor Tu from Bacillus paramycoides - Pei Liu; Haiyu Long; Shuai He; Han Cheng; Erdong Li; Siyu Cheng; Mengdi Liang; Zhengwei Liu; Zhen Guo; Hao Shi (Journal of Zhejiang University-SCIENCE B, 2024)

The effects of dextran in residual impurity on trehalose crystallization and formula in food preservation - Mingxuan Li; Jiahui Li; Xueyou Qin; Jingwei Cai; Ronghua Peng; Mengdi Zhang; Leida Zhang; Wei Zhao; Mingyang Chen; Dandan Han; Junbo Gong (Food Chemistry, 2024)

Exploring the evolutionary mechanism of the cross-regional cooperation of construction waste recycling enterprises: A perspective of complex network evolutionary game - Mengdi Li; Chuanfeng Han; Zhiguo Shao; Lingpeng Meng (Journal of Cleaner Production, 2024)

HvBGlu3, a GH1 β-glucosidase enzyme gene, negatively influences β-glucan content in barley grains - La Geng; Mengdi Li; Shanggeng Xie; Han Wang; Xinyi He; Nannan Sun; Guoping Zhang; Lingzhen Ye (Theoretical and Applied Genetics, 2024)

Astragaloside IV Inhibits Rotenone-Induced α-syn Presentation and the CD4 T-Cell Immune Response - Mengdi Wang; Fengjiao Sun; Xiaofeng Han; Nan Wang; Yalan liu; Jinfeng Cai; Shanshan Tong; Rui Wang; Hongcai Wang (Molecular Neurobiology, 2024)

Identification of Novel Mutations in the Tyrosinase Gene (TYR) Associated with Pigmentation in Chinese Giant Salamanders (Andrias davidianus) - Jie Deng; Mengdi Han; Hongying Ma; Han Zhang; Hongxing Zhang; Hu Zhao; Jia Li; Wei Jiang (Fishes, 2023)
The Chinese giant salamander (Andrias davidianus), an endangered amphibian species endemic to China, has been previously evaluated with regards to its phyletic evolution, zooecology, and ethology, but molecular mechanisms underlying its skin pigmentation remain unknown. Herein, a skin transcriptome database of different colored salamanders was established using RNA-seq, and a total of 47,911 unigenes were functionally annotated. Among these unigenes, a total of 1252 differentially expressed genes (DEGs) were annotated in the seven public databases, and six DEGs were validated by qPCR between five different skin colors and eight tissues. The results showed that TYR, TYRP1, and ASIP were significantly differentially expressed between different body colors, while TYR, TYRP1, and DCT were highly expressed in skin tissue. The full-length complementary DNA of TYR was cloned and analyzed between normal and yellow phenotypes. Three nucleotide sequence deletion sites were identified in the coding region of TYR, leading to premature termination of transcription and translation in yellow individuals. Our study provides useful data for the further study of the molecular mechanisms of melanin formation, and a valuable reference for the breeding of specific skin colors in other salamanders.

Pollution levels and toxicity risks of heavy metals in different reed wetland soils following channel diversion in the Yellow River Delta - Qiutang Wu; Fuhua Bian; Franziska Eller; Mengdi Wu; Guangxuan Han; Junbao Yu; Bo Guan (Wetlands, 2022)

Molecular authentication of medicinal and edible plant Gnaphalium affine (cudweed herb, “Shu-qu-cao”) based on DNA barcode marker ITS2 - Mengdi Zheng; Die Liu; Han Zhang; Yan Zhang (Acta Physiologiae Plantarum, 2021)

Performance evaluation of ensemble learning techniques for landslide susceptibility mapping at the Jinping county, Southwest China - Xudong Hu; Hongbo Mei; Han Zhang; Yuanyuan Li; Mengdi Li (Natural Hazards, 2021)

Microsatellite records for volume 9, issue 3 - Aiguo Yang; Biao Wu; Chao Shen; Guangming Zhang; Hanmiao Liu; Hongying Guo; Jiaman Li; Jinliang Liu; Liqing Zhou; Longbing Rao; Man Yang; Mengdi Li; et al. (Conservation Genetics Resources, 2017)